Coverage of vitamin A supplementation and deworming during Malezi Bora in Kenya - Paloma C. Clohossey; Heather I. Katcher; Geoffrey O. Mogonchi; Nancy Nyagoha; Marissa C. Isidro; Evelyn Kikechi; Edgar E.V. Okoth; Jessica L. Blankenship (Springer, 2019)
Twice-yearly child health weeks are an effective way of reaching children with essential child survival services in developing countries. In Kenya, child health weeks, or Malezi Bora, were restructured in 2007 from an outreach-based delivery structure to a health facility-based delivery structure to reduce delivery costs and increase sustainability of the events. Administrative data from 2007 to 2011 have demonstrated a decrease in coverage of Malezi Bora services to targeted children. A post-event coverage (PEC) survey was conducted after the May 2012 Malezi Bora to validate coverage of vitamin A supplementation (VAS) and deworming and to inform program strategy. Nine hundred caregivers with children aged 6-59 months were interviewed using a randomized, 30 × 30 cluster design. For each cluster, one facility-based health worker and one community-based health worker were also interviewed. Coverage of VAS was 31.0% among children aged 6-59 months and coverage of deworming was 19.6% among children aged 12-59 months. Coverage of VAS was significantly higher for children aged 6-11 months (45.7%, n = 116) than for children aged 12-59 months (28.8%, n = 772) (p < 0.01). Eighty-five percent (51/60) of health workers reported that Malezi Bora was implemented in their area while 23.6% of primary caregivers reported that Malezi Bora occurred in their area. The results of this PEC survey indicate that the existing Malezi Bora programmatic structure needs to be reviewed and reformed to meet WHO guidelines of 80% coverage with VAS.